1995
DOI: 10.1128/jb.177.2.364-371.1995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a mutant strain of Saccharomyces cerevisiae with a deletion of the RAD27 gene, a structural homolog of the RAD2 nucleotide excision repair gene

Abstract: We have constructed a strain of Saccharomyces cerevisiae with a deletion of the YKL510 open reading frame, which was initially identified in chromosome XI as a homolog of the RAD2 nucleotide excision repair gene (A. Jacquier, P. Legrain, and B. Dujon, Yeast 8:121-132, 1992). The mutant strain exhibits increased sensitivity to UV light and to the alkylating agent methylmethane sulfonate but not to ionizing radiation. We have renamed the YKL510 open reading frame the RAD27 gene, in keeping with the accepted nome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
258
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(278 citation statements)
references
References 40 publications
17
258
0
3
Order By: Relevance
“…In order to test if E176A showed an induced or spontaneous mutator phenotype, the WT, rad27⌬ and E176A strains were subjected to treatment with methylmethane sulfonate and UV irradiation. The mutant E176A is resistant to both DNA-damaging agents, indicating that it has an intact DNA repair function, as compared with rad27⌬, which shows sensitivity to both of them (40). E176A strain also did not show any spontaneous mutations when subjected to hom3-10, lys2-Bgl, and canavinine assays, whereas rad27⌬ strain showed a high rate of spontaneous mutations, as previously reported (23) (Table 4).…”
Section: Concerted Action Of Exo and Gen Activities Resolves (Gaa) N supporting
confidence: 63%
“…In order to test if E176A showed an induced or spontaneous mutator phenotype, the WT, rad27⌬ and E176A strains were subjected to treatment with methylmethane sulfonate and UV irradiation. The mutant E176A is resistant to both DNA-damaging agents, indicating that it has an intact DNA repair function, as compared with rad27⌬, which shows sensitivity to both of them (40). E176A strain also did not show any spontaneous mutations when subjected to hom3-10, lys2-Bgl, and canavinine assays, whereas rad27⌬ strain showed a high rate of spontaneous mutations, as previously reported (23) (Table 4).…”
Section: Concerted Action Of Exo and Gen Activities Resolves (Gaa) N supporting
confidence: 63%
“…Mutations in RTHl (RAD27) cause a mutator phenotype (Johnson et al 1995;Reagan et al 1995;Vallen and Cross 1995) that in one study was shown to be as strong as that caused by mutations in MSH2, MLH1, and PMS1 (Johnson et al 1995). This result seems at odds with mechanistic studies of mismatch repair promoted by human cell extracts indicating that, like the E. coli reaction, eukaryotic mismatch repair is likely to involve redundant 5' + 3' and 3' + 5' exonucleases (Modrich 1991;Fang and Modrich 1993;Modrich and Lahue 1996).…”
Section: Other Components Required For Mismatch Repairmentioning
confidence: 99%
“…One possible interpretation of this result is that RTHl functions in an entirely different pathway from MSH2, MLH1, and PMSI . Additional genetic analysis of R THl (RAD27) has indicated that RTHl (RAD27) plays a role in repair of other types of DNA damage, that RTHl (RAD27) is a member of the RAD6 epistasis group that functions in DNA damage tolerance, and that rthl (rad27) mutants also have a cell cycle defect (Reagan et al 1995;Vallen and Cross 1995). Studies of the S. cerevisiae (called RTH1, RAD27, YKL510) and human (called FEN-1, MF-1, exonuclease IV) protein have suggested that RTHl functions in the processing of 5' ends of Okazaki fragments and processing branched DNA structures formed by different DNA repair pathways (Ishimi et al 1988;Harrington and Lieber 1994;Hiraoka et al 1995;Sommers et al 1995).…”
Section: Other Components Required For Mismatch Repairmentioning
confidence: 99%
“…In addition, Fen1 possesses 5' ± 3' exonuclease activity speci®c for double stranded DNA Lieber, 1994a, 1995). The S cerevisiae homologue of Fen1, RAD27 (RTH1, YKL510) shares many characteristics with genes known to be involved in DNA replication (Reagan et al, 1995;Sommers et al, 1995). rad27 deletion mutants show a slow growth rate, and are temperature sensitive with a terminal phenotype characteristic of a defect in DNA replication (Reagan et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, these mutants show high sensitivity to the alkylating agent MMS, with only slight sensitivity to g and u.v. irradiation, suggesting that RAD27 may also play a role in base excision repair (Reagan et al, 1995;Sommers et al, 1995). Mutations in S pombe rad2, which encodes a Fen1 homologue, can be complemented by expression of human Fen1 (rad2 hs ) (Murray et al, 1994).…”
Section: Introductionmentioning
confidence: 99%